2015
DOI: 10.1920/wp.ifs.2015.1510
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of school funding and inputs in England: 1993-2013

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…Year‐by‐year changes in expenditure may not necessarily translate into meaningful changes in school investments, as school administrators might be reluctant to make binding decisions, such as hiring teachers, and instead spend extra funds on one‐off items. However, the period 2007–2010 that is covered by our paper poses an important exception, as the MFG factor was announced in advance for a 3‐year period, giving schools the security of a longer planning horizon (Sibieta, ). Indeed, in the four years that are covered by our empirical application, 25% of spending increases (measured as 3‐year averages of the current and two preceding years) went to teachers, 24% to teaching assistants and 51% to other items.…”
Section: Institutional Backgroundmentioning
confidence: 99%
“…Year‐by‐year changes in expenditure may not necessarily translate into meaningful changes in school investments, as school administrators might be reluctant to make binding decisions, such as hiring teachers, and instead spend extra funds on one‐off items. However, the period 2007–2010 that is covered by our paper poses an important exception, as the MFG factor was announced in advance for a 3‐year period, giving schools the security of a longer planning horizon (Sibieta, ). Indeed, in the four years that are covered by our empirical application, 25% of spending increases (measured as 3‐year averages of the current and two preceding years) went to teachers, 24% to teaching assistants and 51% to other items.…”
Section: Institutional Backgroundmentioning
confidence: 99%
“…These differences in spending per pupil across schools by social deprivation have already been documented (Sibieta, 2015b). To investigate the drivers of the phenomenon in more detail, Figure 5.6 seeks to illustrate the differences and changes in spending per pupil by social deprivation within local authorities.…”
Section: Across Schoolsmentioning
confidence: 87%
“…In previous work, we have sought to detail how the increase in day-to-day spending over the 2000s translated into actual inputs (Sibieta, 2015b). We showed that around 20-30% of the increase in spending translated into greater numbers of teachers and higher teacher pay per head.…”
Section: Long-run Trends In Per-pupil Expenditurementioning
confidence: 95%
“…However, in England, spending per pupil was protected in real terms (Sibieta, 2015). The Coalition Government also introduced and developed a raft of education policies.…”
Section: Education Policy Under the Coalition Government 2010-15mentioning
confidence: 99%
“…Central control of the pupil premium grant is not direct; rather, Ofsted reports on its use when it inspects schools. These changes resulted in higher levels of funds being targeted at more deprived schools between 2010 and 2013 (Sibieta, 2015). In Wales a similar grant for disadvantaged pupils, the pupil deprivation grant (PDG), was launched in 2012; this too was designed to help close the attainment gap (Welsh Government, 2014a).…”
Section: Funding Schools and The Pupil Premiummentioning
confidence: 99%